La casa del lago : Berlín, una casa, cinco familias, cien años de historia - Harding, Thomas, 1968- (Serie Ensayo (Galaxia Gutenberg (Firm)), 2017)
"In the summer of 1993, Thomas Harding traveled to Germany with his grandmother to visit a small house by a lake on the outskirts of Berlin. It had been a holiday home for her and her family, but in the 1930s, she had been forced to flee to England as the Nazis swept to power. Nearly twenty years later, the house was government property and soon to be demolished. It was Harding's legacy, one that had been loved, abandoned, fought over -- a house his grandmother had desired until her death. Could it be saved? And should it? As Harding began to make inquiries, he unearthed secrets that had lain hidden for decades about the lives of the five families who had lived there: a wealthy landowner, a prosperous Jewish family, a renowned composer, a widow and her children, and a Stasi informant. All had made the house their home, and all -- bar one -- had been forced out. The house had been the site of domestic bliss and of contentment, but also of terrible grief and tragedy. It had weathered storms, fires and abandonment; witnessed murders, had withstood the trauma of a world war, and the dividing of a nation. As the story of the house began to take shape, Harding realized that there was a chance to save it, but in doing so, he would have to resolve his own family's feelings towards their former homeland -- and a hatred handed down through the generations. -- For readers of Edmund de Waal, Daniel Mendelson, and David Laski"--Provided by publisher.